Generalized financial cycle theory from the Minsky’s perspective: UK 1270–2016 - Porada-Rochoń, Małgorzata; Škare, Marinko (Journal of Business Economics and Management, 2020)
Our study aims to bridge the gap between contemporary studies on financial cycles and the financial instability hypothesis in the form of a Minsky cycle (Minsky, 1963). Paper contribution range from explored causality links (financial cycles cause business cycles) to the empirical estimation of the Minsky moment. We use Braitung and Candelon (2006) Granger causality test and discrete threshold model (Hansen, 2005) to the link between financial and business cycles in the UK from 1270–2016. Financial and business cycles relation varies over time with contemporary financial cycles being longer to their historical versions. Financial cycles lead business cycles. Business cycles are an economy reaction to them and change in the Minsky moment. Minsky moment has a statistically significant impact on main growth determinants – population, export, technology. Policymakers should look for the Minsky moment when setting up a new economic policy to assure it will be an effective one.